FORMATION OF STUDENTS' ETHNIC TOLERANCE IN INSTITUTIONS OF HIGHER EDUCATION - Marija Czepil; Oresta Karpenko; Alla Revt; Kateryna Istomina (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
Ethnic tolerance is one of key issues of global and national order and is considered to be one of the necessary conditions for effective professional training. The aim of our research was to determine the background factors of students' ethnic tolerance, its components and levels. Using two methods - Tolerance Index by Soldatova and our own questionnaire - allowed us to determine tolerance level in students of pedagogical specialties of Lviv region universities in Ukraine. We identified some fundamental factors of the effective formation of tolerance: the acceptance of cultural and national features of an individual, the ability to constructive cooperation and dialogue regardless of ethnicity, the ability and desire to listen to the interlocutor and understand his point of view. In the process of learning, students acquire the initial skills of professional and social communication and master the foundations of tolerant behaviour. The formation of ethnic tolerance is facilitated by the following factors: family upbringing, positive communication with representatives of other nationalities, knowledge of cross-cultural differences, travelling to other countries, studying at a higher education institution.